Enhancing the viability of maritime arbitration for trade dispute resolution in Tanzania - Edrick Johansen Mugisha; Msabaha Juma Mwendapole; Werneld Egno Ngongi; Diana Kiwia (Transportation Research Interdisciplinary Perspectives)
Maritime arbitration holds untapped potential for transforming trade dispute resolution within Tanzania’s vital maritime sector. Despite its advantages of speed, cost-effectiveness, and specialized expertise, the adoption of maritime arbitration remains limited due to legal, institutional, and awareness-related barriers. This study explores the current state of maritime arbitration in Tanzania, identifying key challenges such as insufficient legal frameworks, limited awareness among stakeholders, and a shortage of trained arbitrators. Through a qualitative approach, involving interviews, surveys, and a comprehensive review of legal documents, the research offers actionable insights to enhance arbitration’s effectiveness in resolving disputes. The findings highlight the need for targeted reforms, including aligning national laws with international standards, establishing training programs for arbitrators, and promoting awareness of arbitration’s benefits to the maritime community. These improvements promise not only faster and more cost-efficient dispute resolution but also a boost to Tanzania’s regional trade competitiveness. By fostering a transparent and predictable arbitration environment, Tanzania can position itself as a strategic hub for maritime trade in East Africa, attracting international investors and strengthening its role in global supply chains. The study’s recommendations offer a blueprint for other emerging maritime economies seeking to elevate their dispute resolution frameworks, emphasizing the broader relevance of Tanzania’s approach in shaping more integrated and resilient maritime sector worldwide.